4. Jantanisasi Anakan Ikan Guppy (Poecilia reticullata) Melalui Perendaman Induk dengan Larutan 17-Metiltestosteron - M Istuanto; Ferdinand Hukama Taqwa; M Syaifudin; Muslim Muslim (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2016)
This study aimed to investigate the effect of different 17α-methyltestosterone concentrations toward the ratio of male guppy fish seedlings. This study was implemented in  Laboratory of Local Fish Hatchery of Gandus, Palembang. The research method used was complete random design consisting of 4 treatments and 3 repetitions. The implemented treatments were guppy fish parent soaking in 17α-methyltestosterone solution of various concentrations namely: 0 mg.L-1 (D0), 2.5 mg.L-1 (D1), 5 mg.L-1 (D2), and 7.5 mg.L-1 (D3). The observed parameters consisted of percentage of male seedlings and viability of guppy fish seedlings during the raising as well as physical-chemical parameters (temperature, pH, and dissolved oxygen). The trial result indicated that the administration of 5 mg.L-1 (D2) of 17α-methyltestosterone solution could increase the percentage of male guppy fish seedlings up to 55.40% and quite high viability during the raising for 83.79%. The range of physical-chemical water value during this study still supported the raising of parents and seedlings of guppy fish. Keywords : guppy,  hormon, 17α-metiltestosteron